Cathodic cage plasma nitriding of AISI M3:2 steel: evaluation of the treatment atmosphere effect - de Carvalho, Júlio Fernando Sousa; de Sousa Brito, Marcos Cristino; da Silva, Lucas Pereira; de Sousa, Rômulo Ribeiro Magalhães (Disciplinarum Scientia | Naturais e Tecnológicas, 2025)
Samples of AISI M3:2 steel were subjected to plasma nitriding using a cathodic cage, with variations in gas flow during pre-treatment and treatment to assess its influence on the properties of the resulting coatings. After nitriding, the samples were analyzed using X-ray diffraction (XRD), Vickers microhardness testing, and optical microscopy. XRD analysis revealed the formation of iron and chromium nitrides in all treated samples. Although the layer was not particularly thick, as observed in optical microscopy measurements, there was a significant increase in microhardness, with one sample exhibiting a hardness three times greater than that of the untreated material. The results demonstrate the potential of the cathodic cage nitriding technique to improve the surface mechanical properties of AISI M3:2 steel.